Language Education Activties for Young Preschoolers Involving Embodied Cognition Versus Traditional Language Education Activities for Young Preschoolers - Maria-Cristina Manea; Mușata-Dacia Bocoș (Babes-Bolyai University, 2023)
Currently, in contemporary cognitive science, embodied cognition is a controversial research topic. This article draws a parallel between how early childhood teachers conduct early language education activities involving embodied cognition and how they conduct traditional language education activities. Language education activities involving embodied cognition are empirically supported, engage the motor system, the perceptual system and make use of elements of the proximal environment. Traditional language teaching activities are purely theoretical and do not lead preschoolers to deepen and extend connections so that they can make connections between sound perception and word meaning. Our interest in the current approach was to collect descriptive data from preschool teachers in Romania in order to identify strengths and weaknesses of language education activities involving embodied cognition and traditional language education activities. It also aimed to identify, for the teachers involved in the research, the difficulties that young preschoolers encounter in the process of comprehension of new words and pronunciation. We believe that understanding word meaning and pronunciation are processes that underpin effective language teaching. The method used was the survey and the research instrument applied, the questionnaire. The study involved 224 pre-school teachers from eight counties in the country, namely Alba, Arad, Bihor, Caraș-Severin, Cluj, Gorj, Hunedoara and Timiș.